(untitled) (Scientific journal of the Fergana State University, 2023)
The observation of medical euphemisms in the Uzbek language revealed that they differ according to the specifics of speech of different social strata and professions. Medical euphemisms can be divided into the following groups based on their adaptation to social stratum speech. The choice and application of euphemisms in the communication process often depends on social factors. This is mainly influenced by factors such as social class, social role, social status, sex. Although medical euphemisms in the Uzbek language differ in the nature of age, they do not distinguish the age characteristics of the subject of speech. According to the differential signs of age in the sense of euphemism, 1) the sign of "childhood"; 2) marked "belonging to adolescence"; 3) marked "middle-aged"; 4) marked "old age"; 5) “age-appropriate” neutral medical euphemisms are distinguished.